A panel co integration analysis of bank profitability and bank-specific variables in Islamic banks - Sapuan, Noraina Mazuin; Ramli, Afdzal Aizat; Roly, Mohammad Rahmdzey (2013)
In line with the increasing demand for Islamic banking products in Malaysia, this study intended to measure the long run and short run relationship of Islamic banking profitability with bank-specific variables and financial structure. The analysis applied recently developed panel unit root and panel cointegration techniques for dynamic panel estimations. The data are utilized from 12 Islamic banks in Malaysia from the period of 1996 to 2010. The result from Pedroni’s heterogenous panel of cointegration revealed that bank profitability, bank specific variables and financial structure are cointegrated in the long run.